1999
DOI: 10.1002/jlb.65.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between phosphatidic acid and cyclic nucleotide phosphodiesterases in activated human blood mononuclear cells

Abstract: Abstract:We have previously shown that mitogenic activation of human PBMC rapidly increases both the intracellular phosphatidic acid (PA) level and cyclic nucleotide phosphodiesterase (PDE) activity, with time-course responses, suggesting a causative relationship between the two events. PA also directly stimulated cAMP-PDE activity in acellular systems. Thus the mitogenic properties of PA might be due to its ability to lower the level of cAMP, a negative effector of lymphocyte activation, through PDE activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Our data also suggest that this mechanism is relevant to human physiology, given the significant correlations between adipose tissue lipin 1 expression and lipolytic rates and PKA signaling in obese human subjects. Previous work on PA-mediated regulation of intracellular signaling events, including allosteric activation of mTOR (22) and PDE4 (20,25), linked the activity of PLD and DAG kinase enzymes to controlling this "signaling pool" of PA. An important finding of the present study is that the pool of PA dephosphorylated by lipin 1 that is likely destined for phosphoglycerolipid synthesis can regulate mTOR and PDE4 activity as well. It should be noted that PA was recently found to suppress formation of the mTORC2 complex (26); thus, further work is needed to determine whether mTORC1 is specifically activated by this pool of PA. We also acknowledge that we cannot rule out the possibility that alterations in other lipid species upstream or downstream of PA in these pathways are mediating these signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also suggest that this mechanism is relevant to human physiology, given the significant correlations between adipose tissue lipin 1 expression and lipolytic rates and PKA signaling in obese human subjects. Previous work on PA-mediated regulation of intracellular signaling events, including allosteric activation of mTOR (22) and PDE4 (20,25), linked the activity of PLD and DAG kinase enzymes to controlling this "signaling pool" of PA. An important finding of the present study is that the pool of PA dephosphorylated by lipin 1 that is likely destined for phosphoglycerolipid synthesis can regulate mTOR and PDE4 activity as well. It should be noted that PA was recently found to suppress formation of the mTORC2 complex (26); thus, further work is needed to determine whether mTORC1 is specifically activated by this pool of PA. We also acknowledge that we cannot rule out the possibility that alterations in other lipid species upstream or downstream of PA in these pathways are mediating these signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…The sense and antisense primers were 5Ј-GGGATCCGTGTGAAGCGGGTCACTTCAGGACC-G-3Ј and 5Ј-GGGAATTCTCTGGTTTCCCCATGCAGCTCTCCCAC-3Ј, respectively. Primers to specifically amplify PLD2 transcripts were designed on the basis of published human sequences (27) Caldwell et al (28) as described previously (29). After glycerol treatment, the cells were pelleted at 900 ϫ g for 10 min, resuspended in lysis buffer (20 mM Hepes, 25 mM sucrose, 0.1 mM EGTA, 0.05 mM phenylmethylsulfonyl fluoride, 10 units/ml aprotinin, 2 g/ml pepstatin A, pH 7.4), and stored frozen at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although some reports have described an activation of PLD following ligation of the TCR/CD3 complex (6, 7), other studies failed to demonstrate efficient CD3 coupling to PLD, either in normal peripheral lymphocytes (8) or in T cell lines (9). It has been shown that TCR ligation was accompanied by a fast and large increase in PA level occurring in the first minutes of T cell activation (10,11). However, this early peak could be attributed to PA derived from DAG through the sequential activation of phospholipase C-␥ and DAG kinase because it was totally suppressed by DAG kinase inhibitors (10,11).…”
Section: Disruption Of Lipid Rafts Stimulates Phospholipase D Activitmentioning
confidence: 99%
“…It has been shown that TCR ligation was accompanied by a fast and large increase in PA level occurring in the first minutes of T cell activation (10,11). However, this early peak could be attributed to PA derived from DAG through the sequential activation of phospholipase C-␥ and DAG kinase because it was totally suppressed by DAG kinase inhibitors (10,11). Only when phospholipids of lymphocyte membrane were modified by enrichment with DHA (5,12) or the monohydroxylated derivative of arachidonic acid, 12-HETE (13), were we able to observe PLD activation following mitogenic stimulation.…”
Section: Disruption Of Lipid Rafts Stimulates Phospholipase D Activitmentioning
confidence: 99%